Evaluation Of The Quality Of The Online Sales Application Of Light Steel Material Using The Mccall Quality Factors Method - Kristian Mulia, Johan; Sutomo, Rudi (International Journal of Science, Technology & Management, 2023)
We are unable to survive without technology in today's entirely digital environment. Especially when managing corporate activities that depend on technology, hardware or software can be used in the technology. This business manufactures items out of mild steel. The prioritized products include roof trusses, building frame columns, and metal roof tiles. This business uses soft steel elements to provide three applications to support online sales. But because the organization has yet to conduct any testing, there are still a lot of faults or problems, making it necessary to manually assess the mobile application until a scenario report is generated and the testing findings are implemented. Scenario photographs and error sections make up the data that was collected. Based on this, the application's quality has been assessed to determine the correctness, comprehensiveness, and standard of the software used in the Metalmens Application. However, the system's quality still needs to be discovered. The McCall method is used as the measurement technique in this investigation. According to the McCall Method results, the quality of Metalmen Applications is solid, scoring 84%, with dependability scoring 84% and reliability scoring 62%. Dependability is the best indicator, scoring 84%.